EFEITO DA ADIÇÃO E Pd E Ru SOBRE CATALISADORES Mo/H-ZSM-5 NA CONVERSÃO DIRETA DO METANO A HIDROCARBONETOS - Sily, Priscila Dias (2006)
Each year, new reserves of natural gas have been discovered, and natural gas became a large source of raw material. In the last decade, new routes of valorization of natural gas have been studied, including direct conversion of methane, main component of natural gas, to hydrocarbons. The present study aimed to investigate the Ru, Pd and Mo catalysts supported in H-ZSM-5, comparing their activity, selectivity and stability in the dehydro-aromatization of methane. The tested catalysts were: Mo/H-ZSM-5, PdMo/HZSM- 5, RuMo/H-ZSM-5, RuPdMo/H-ZSM-5, Pd/H-ZSM-5 and Ru/H-ZSM-5. As characterization techniques were employed: UV-vis diffuse reflectance (DRS), temperature-programmed reduction (TPR), temperature-programmed surface reaction (TPSR) and temperature-programmed oxidation (TPO). The catalysts were also evaluated in the test catalytic. The DRS spectra, as well as the TPR profiles evidenced the presence of isolated tetrahedric species of Mo(VI) in Mo/H-ZSM-5 catalyst even when Pd and Ru are added to the system. The TPR profiles also evidenced that Pd addition to Mo/H-ZSM-5 catalyst decreases the reduction temperature due to the formation of a Pd-Mo complex. The catalytic tests, TPSR and TPO experiments showed that Pd based catalysts were more selective to naphthalene and suffered strong deactivation. The additions of Ru to Mo/HZSM- 5 catalysts improved the activity and stability, avoiding the carbonaceous deposit and probably due to a mechanism of protection of Mo2C surface.